2012
DOI: 10.1007/s10499-011-9496-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lipid-enriched Artemia on the reproductive performance of the white-striped cleaner shrimp, Lysmata amboinensis

Abstract: Broodstock maturation diets are an important component of shrimp hatchery management, since the nutritional status of spawners can impact on gonadal maturation, egg fecundity, embryo hatchability and overall larval quality. The ability to manipulate the biochemical composition of Artemia to deliver key nutrients to cultured animals has rendered their inclusion in broodstock feeds increasingly common. Lipid enrichment of Artemia to boost their highly unsaturated fatty acid (HUFA) content is a standard procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…Tziouveli et al (2011) suggested that the high DHA level in squid may partly clarify the effect of lesser egg cover prior to hatch conceding egg production in L. amboinensis. Tziouveli et al (2012) later showed that DHA content of 11% administered to broodstock of L. amboinensis contributed the optimal outcome for embryo hatchability, as well as succeeding larval production. Figueiredo et al (2008) reported that low consumption of DHA during embryogenesis based on fatty acid profiles of A. cinereum eggs showed that there may not be a requirement for DHA-rich diet for this specie.…”
Section: Resultsmentioning
confidence: 99%
“…Tziouveli et al (2011) suggested that the high DHA level in squid may partly clarify the effect of lesser egg cover prior to hatch conceding egg production in L. amboinensis. Tziouveli et al (2012) later showed that DHA content of 11% administered to broodstock of L. amboinensis contributed the optimal outcome for embryo hatchability, as well as succeeding larval production. Figueiredo et al (2008) reported that low consumption of DHA during embryogenesis based on fatty acid profiles of A. cinereum eggs showed that there may not be a requirement for DHA-rich diet for this specie.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Tziouveli et al (2012) reported a low fertility (from 49 to 529 larvae) in female cleaner shrimp L. amboinensis following feeding with a high dietary lipid content (20% and 22% lipids); in contrast, a study by Calado et al (2009) (Guerrero & Sandoval, 2012). Moreover, the shrimps fed this diet (40/8) produced 100% viable spawn.…”
Section: Discussionmentioning
confidence: 96%
“…Authors such as Calado, Rosa, Morais, Nunes, and Narciso. (); Cunha, Mascaro, Chiapa, Costa, and Simoes (); Tziouveli, Hall, and Smith () have observed that using fresh or frozen diets increases efficiency of gonadal maturation and fertility in shrimp of the genus Lysmata sp; however, fresh diets can cause nutritional deficiencies in the long term, thus, for the sustainable production of the ornamental shrimp, it is necessary to establish optimum nutritional requirements and formulate diets according to their life stage. It is important to consider that the nutritional requirements of crustaceans can vary as a function of several factors such as age, sex, feeding habits and environmental conditions; therefore, we have to include these variables to obtain accurate results, since the protein and lipid requirements can vary among species of the same genus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations